On the Issue of Human Capital of the Working Older Generation of Modern Russia - V. Moiseev, A.Vladimir; S. Kolesnikova, Julia; V. Yagudina, Elena; V. Yurkov, Dmitry; R. Valeev, Emil (Journal of Ecohumanism, 2024)
Practice has shown that the onset of retirement and pre-retirement age in modern Russia adds new problems to the working older generation, caused by significant changes in lifestyle and new views on human labor activity. The implemented pension reform in Russia, which added five years to the day of retirement, significantly exacerbated the problems associated with the employment of people of retirement age. The article offers scientifically based recommendations for increasing human capital at the expense of the working older generation, taking into account regional and other characteristics. In modern conditions, human capital can play an important role in solving many problems during the military conflict between Russia and Ukraine, especially in increasing the military-industrial potential of our state. In conditions of labor shortage, experienced personnel of engineers, technologists, managers can significantly strengthen Russian industrial and other enterprises